Strengthening nutrition interventions during antenatal care improved maternal dietary diversity and child feeding practices in urban Bangladesh: Results of a quasi-experimental evaluation study - Nguyen, Phuong Hong; Sununtnasuk, Celeste; Christopher, Anita; Ash, Deborah; Ireen, Santhia; Kabir, Rowshan; Mahmud, Zeba; Ali, Mohsin; Forissier, Thomas; Escobar-DeMarco, Jessica; Frongillo, Edward A.; Menon, Purnima (Elsevier, 2023)
Background: Bangladesh is urbanizing rapidly, facing challenges of malnutrition, low coverage and poor quality of urban nutrition services. Objectives: We assessed the impact of integrating maternal, infant, and young child nutrition interventions, delivered at urban Maternal Neonatal and Child Health facilities, on maternal dietary diversity, iron-folic acid (IFA) and calcium consumption, and child feeding practices. Methods: We used a quasi-experimental design with a non-random assignment of 20 health facilities in Dhaka to intensive and standard service arms. We conducted facility-based observations and community-based surveys at baseline (2020) and endline (2022) (n=2,455 observations and surveys with 1,678 pregnant [PW] or recently delivered women [RDW] at endline). We derived difference-in-difference (DID) estimates, adjusted for characteristics that differed at baseline or endline, and accounted for clustering. Results: Exposure to antenatal care (ANC) was similar in both arms: two-thirds of RDW received ANC during the first trimester and three-fourths received ≥4 ANC check-ups. Compared to the standard arm, a higher proportion of PW in the intensive arm received counselling on dietary diversity (DID: 45 percentage points [pp]), and a higher proportion of RDW received IFA (25pp) and calcium supplementation (19pp), adequate weight gain (44pp), and appropriate child feeding (27pp). Improvements were greater in the intensive than standard arm for number of food groups consumed (DID: 1.1 food groups) and minimum dietary diversity (23pp); no impact was observed for IFA and calcium consumption during pregnancy. Impacts were observed for early initiation (20pp), exclusive breastfeeding (45pp), introduction of solid or semi-solid foods (28pp), and egg and/or flesh food consumption (33pp) among children. Minimum dietary diversity and acceptable diet remained low in both arms. Conclusions: Intensifying nutrition in government-aligned health services delivered by experienced NGO-run facilities is a feasible model to address the urban health gap, nutrition services coverage, and improved practices.